A new species of planthopper in the genus Anotia (Hemiptera: Auchenorrhyncha: Derbidae) from the Los Angeles cloud forest in Costa Rica - Bahder, Brian W.; Echavarria, Marco A. Zumbado; Barrantes, Edwin A. Barrantes; Helmick, Ericka E.; Kunz, Gernot; Bartlett, Charles R. (Zootaxa, 2023)
Recent survey work in Costa Rica has resulted in the discovery of new species of derbid and cixiid planthoppers associated with palms. During this survey, one species belonging to the genus Anotia has been discovered and described, A. firebugia. A second species was collected while sweeping trailside vegetation in the Los Angeles cloud forest in Costa Rica and determined to represent a new species of Anotia. Herein, Anotia cerebro sp. n. is described and supplemental molecular data for the cytochrome c oxidase subunit I (COI), 18S rRNA gene and D9-D10 expansion region of the 28S rRNA gene are provided.